The construction of the social institutions and gender index (SIGI) - Boris Branisa; Stephan Klasen; Maria Ziegler (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2009)
In this paper we construct the Social Institutions and Gender Index (SIGI) using variables of the OECD Gender, Institutions and Development database. Instead of measuring gender inequalities in education, health, economic or political participation, the SIGI allows a new perspective on gender issues. It is a composite measure of social institutions which are mirrored by societal practices and legal norms that produce inequalities between women and men in non-OECD countries. Empirical results confirm that the SIGI provides additional information to that of other wellknown gender-related indices.
Keywords: D63; I39; J16; 330; SIGI; Composite index; Gender inequality; Social institutions; OECD-GID database; Geschlechterdiskriminierung; Soziale Norm; Institutionalismus; Indexberechnung; OECD-Staaten; Welt